2015
DOI: 10.1590/1807-1929/agriambi.v19n9p865-870
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of strawberry plants fertilized with nitrogen and phosphorus

Abstract: A B S T R A C T Strawberry (Fragaria x ananassa)is a crop that has rapid growth and is highly influenced by fertilization. Due to its development speed, the plant needs to absorb sufficient macronutrients in order to meet its demand. The objective of this research was to evaluate growth and yield of strawberry under different doses of nitrogen (N), phosphorus (P) and potassium (K) fertilization. The treatments, using Box's central composite design, were distributed in randomized blocks with four replicates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
1
14
0
2
Order By: Relevance
“…P negatively influenced titratable acidity, a result which agrees with that which has been reported by Obreza [ 53 ] in citrus. In addition, Medeiros et al [ 70 ] and Ahmad et al [ 71 ] also found this effect in strawberry, observing that low concentrations of P produce high titratable acidity in the fruit.…”
Section: Resultsmentioning
confidence: 88%
“…P negatively influenced titratable acidity, a result which agrees with that which has been reported by Obreza [ 53 ] in citrus. In addition, Medeiros et al [ 70 ] and Ahmad et al [ 71 ] also found this effect in strawberry, observing that low concentrations of P produce high titratable acidity in the fruit.…”
Section: Resultsmentioning
confidence: 88%
“…A lower ratio was obtained from the fertilization of N and K 2 O primarily because the interactive effects of these mineral nutrients are necessary as the former improved yield while the latter improved fruit quality [16]. The application of N and P alone results in a lower yield than with a complete NPK application [17]. The importance of K is vital since it participated in many metabolic activities such as fruit quality improvement and stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…El P juega un papel importante en todos los procesos metabólicos que participan en la transferencia de energía, dentro de los que se encuentra la formación de hojas, de flores, de frutos y de órganos reproductivos, como los estolones; esto se pudo observar en la presente investigación, en donde el fosfato térmico utilizado participó activamente en la formación de estolones, considerada como una variable de gran importancia, a nivel de rendimiento . Medeiros et al . (2015) indican que la fresa es una especie en la que la nutrición fosfórica es muy importante, ya que influye sobre variables de crecimiento, número y peso de frutos, como también en el número y en el desarrollo de hojas, que son favorecidos por suministro de altos niveles de este nutrimento .…”
Section: Resultados Y Discusiónunclassified